The cono-dos and cono-dont's of phosphatic microfossil preparation and microanalysis - Shirley, Bryan; Bestmann, Michel; Jarochowska, Emilia (Micron, 2020)
Scanning electron microscope (SEM) imaging of fossils allows unlocking ultrastructural information about their skeletal tissues, but sample preparation of biominerals forming their skeletons requires time, patience, and knowledge. SEM and associated analytical methods allow the observation of internal microstructure, shedding light on function, growth and chemistry. Sample preparation is the process by which material is fixed within a medium (e.g. epoxy resin), a transect created and surface defects removed. This step is arguably the most important in any SEM-based analysis, allowing for the acquisition of reliable, high quality data sets. When conducting any SEM-based technique, the presence of a flat surface is needed to collect consistent and reliable data. Surfaces with topography will both induce charging effects but will also compromise the reliability of data acquired. Techniques from material science are continuously adapted to palaeontological applications, in particular with respect to calcareous microfossils. However, similar studies have not been extensively conducted on bioapatite, owing in part to the difficulties faced in sample preparation alongside its susceptibility to electron beam damage. This case study focuses on conodonts, a marine vertebrate group ranging from the late Cambrian to the Late Triassic. They have been chosen as a model due to the abundance of material, complexity of internal tissues and previous work focused on histological features. With these phosphatic microfossils, we attempt to outline the process of sample preparation and provide information on how to avoid and overcome common pitfalls.
CRIS-Team Scopus Importer:2020-09-04
Keywords: Conodont; Microanalysis; Preparation; Scanning electron microscopy; Ultrastructure